2015
DOI: 10.4081/ijas.2015.3624
|View full text |Cite
|
Sign up to set email alerts
|

Pathways Towards to Improve the Feasibility of Dairy Pastoral System in La Pampa (Argentine)

Abstract: Over the last decade, pastoral systems have been intensified in response to an increasing demand for meat and milk, by generating environmental and social problems due to its high dependence on external inputs. The objective of this research was to analyze the economic feasibility of dairy pastoral system in La Pampa (Argentina). The main successful factors were identified through technical efficiency analysis, and subsequently improvement actions were suggested. The technique data envelopment analysis creates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 35 publications
0
18
0
2
Order By: Relevance
“…Large-scale farms generate various effects; Steinfeld et al (2006), Gerber et al (2013) and Angón et al (2015) suggest that when farms are more specialized in both dimension and intensification tend to increase production volumes, herd size, and productivity, but the number of farms in the territory was significantly reduced. In this regard Udo et al (2011) and Oosting et al (2014) indicated that a considerable part of the smallholders in a village would not be part of the development; some of them will have to become labourers in their community or migrate to urban areas to find employment as effects of increased dimension in long term ("stepping out" strategy by Dorward et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large-scale farms generate various effects; Steinfeld et al (2006), Gerber et al (2013) and Angón et al (2015) suggest that when farms are more specialized in both dimension and intensification tend to increase production volumes, herd size, and productivity, but the number of farms in the territory was significantly reduced. In this regard Udo et al (2011) and Oosting et al (2014) indicated that a considerable part of the smallholders in a village would not be part of the development; some of them will have to become labourers in their community or migrate to urban areas to find employment as effects of increased dimension in long term ("stepping out" strategy by Dorward et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…According to Gerber et al (2013) animal management practices and technologies determine the level of productivity. Angón et al (2015) propose improving technological practices in the grazing dairy system in La Pampa (Argentina). Oosting et al (2014) recommend increasing the production and shift from rural to urban market and Cuevas- Reyes et al (2013) highlight that the clustering and a major organization of smallholders could be an access to a pathway of higher added value.…”
Section: Discussionmentioning
confidence: 99%
“…La respuesta de los productores a la situación de crisis ha sido muy diferente. Los cambios se han orientado a incrementar la producción, mano de obra más cualificada, aumento en el uso de tecnologías y reducción progresiva del pastoreo (Angón et al, 2015). Estos cambios estructurales implican un riesgo en la viabilidad de las explotaciones ganaderas, ya que impactan en su carácter multifuncional y reducen el grado de complementariedad existente entre las diferentes actividades (Ryschawy, Choisis, Choisis, Joannon, & Gibon, 2012.…”
Section: Introductionunclassified
“…Estas empresas cuentan con el triple de colmenas y generan el doble de miel; sin embargo, sólo duplican su necesidad de mano de obra (P<0.05). Estos resultados indican la existencia de economías de escala; la mayor dimensión de las unidades de producción viables permite hacer un uso más eficiente del factor trabajo, mientras que aquéllas no viables se sitúan en rendimientos de escala crecientes (27,28) . En el Cuadro 3 se muestra la descripción estadística de las variables categóricas y su asociación con la viabilidad.…”
Section: Resultados Y Discusiónunclassified